Differential activation mechanisms of serum C5a in lupus nephritis and neuropsychiatric systemic lupus erythematosus. Issue 2 (4th March 2017) - Sakuma, Yuko; Nagai, Tatsuo; Yoshio, Taku; Hirohata, Shunsei
Abstract: Objective : To explore the role of C5a in the pathogenesis of neuropsychiatric systemic lupus erythematosus (NPSLE) and lupus nephritis (LN). Methods : Sera were obtained from 29 patients with NPSLE, 25 with LN, 26 without NPSLE or LN [SLE alone], and 21 healthy donors. Cerebrospinal fluid (CSF) was obtained from 29 NPSLE patients. C5a and C5 were measured by ELISA. Blood-brain barrier (BBB) function was evaluated by Q albumin ([CSF albumin/serum albumin] × 10 3 ). Results : Serum C5a, but not C5, was significantly increased in SLE compared with healthy control. Serum C5a, but not C5, was significantly higher in NPSLE and in LN than in SLE alone. Serum C4, but not C3, was lower in LN than in NPSLE. Q albumin was significantly higher in diffuse NPSLE than in focal NPSLE, whereas there were no significant differences in CSF or serum C5a between both groups. Notably, CSF C5 and C5a were significantly correlated with Q albumin, whereas serum C5a, but not C5, appeared to be inversely correlated with Q albumin. Conclusion : These results disclosed that serum C5a was elevated not only in NPSLE but also in LN through different mechanisms. Moreover, it is suggested that C5a might be consumed during BBB damages.